Is temporary employment a risk factor for work disability due to depressive disorders and delayed return to work? The Finnish Public Sector Study - Ervasti, Jenni; Vahtera, Jussi; Virtanen, Pekka; Pentti, Jaana; Oksanen, Tuula; Ahola, Kirsi; Kivimäki, Mika; Virtanen, Marianna (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'Research on temporary employment as a risk factor for work disability due to depression is mixed, and few studies have measured work disability outcome in detail. We separately examined the associations of temporary employment with (i) the onset of work disability due to depression, (ii) the length of disability episodes, and (iii) the recurrence of work disability, taking into account the possible effect modification of sociodemographic factors. ' ' METHODS ': 'We linked the prospective cohort study data of 107 828 Finnish public sector employees to national registers on work disability (>9 days) due to depression from January 2005 to December 2011. ' ' RESULTS ': 'Disability episodes were longer among temporary than permanent employees after adjustment for age, sex, level of education, chronic somatic disease, and history of mental/behavioral disorders [cumulative odds ratio (COR) 1.37, 95% confidence interval (95% CI) 1.25–51). The association between temporary employment and the length of depression-related disability episodes was more pronounced among participants with a low educational level (COR 1.95, 95% CI 1.54–2.48) and older employees (>52 years; COR 3.67, 95% CI 2.83–4.76). The association was weaker in a subgroup of employees employed for ≥50% of the follow-up period (95% of the original sample). Temporary employment was not associated with the onset or recurrence of depression-related work disability. ' ' CONCLUSIONS ': 'Temporary employment is associated with slower return to work, indicated by longer depression-related disability episodes, especially among older workers and those with a low level of education. Continuous employment might protect temporary employees from prolonged work disability.
Keywords: age; depression; depressive disorder; disability; educational level; employment status; Finnish Public Sector Study; recurrence; return to work; risk factor; temporary employment; work disability